(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article seeks to understand the continuities and emergencies of the mobilization and resistance processes of communities linked to the Panguipulli Forest and Timber Complex (COFOMAP). This work analyzes these two elements through historiogra- phic work and the production of collective memories on the social and political project that gave life to said state company in the foothills and the dictatorial fracture that makes a dispute emerge in the present. Specifically, we will refer to the case of groups of former settlers that come together to denounce the forced displacement that they experienced during the military dictatorship, seeking recognition and the recovery of the territory that was deprived of them. Starting from a work of accompaniment, stories and documentary review, we delve into the historical process experienced and the different memories that emerge in the practice of remembering. Thus, we present some reflections to reveal the territory and the different experiences that challenge a memory and history in the current conflict.